Relationship of interleukin‐23 with matrix metalloproteinase‐9, pentraxin‐3, sleep quality and prostate size in benign prostatic hyperplasia - Navaneethakannan, Mathiyazhagan; Nandeesha, Hanumanthappa; Sreenivasan, Sreerag K (Andrologia, 2022)
Benign prostatic hyperplasia (BPH) is known to be associated with sleep disturbance and inflammation. The objective of the study was to assess the levels of serum MMP‐9 and its inhibitor (TIMP‐1), interleukin‐23 and pentraxin‐3 and their association with sleep quality index and prostate size in BPH patients. Eighty‐eight BPH patients were recruited based on clinical and ultrasound findings. MMP‐9 and its inhibitor (TIMP‐1), interleukin‐23 and pentraxin‐3 were estimated in all the subjects. Sleep quality was assessed using Pittsburgh Sleep Quality Index (PQSI). Interleukin‐23 was significantly correlated with prostate size (p = 0.031), TIMP‐1 (p = 0.035), MMP‐9 (p = 0.004) and PSQI score (p = 0.020). TIMP‐1 was significantly correlated with MMP‐9 (p = 0.006) and prostate size (p = 0.016). Pentraxin‐3 was positively correlated with PSQI score (p = 0.047). Multivariate analysis shows that interleukin −23 (p = 0.006) predicts prostate enlargement in BPH patients. Interleukin‐23 was significantly increased in BPH patients with PSQI score >9 compared to those with PSQI <9. We conclude that poor sleep quality contributes to inflammation in BPH. Inflammation leads to prostate enlargement in patients with BPH.